ANALISA PRODUKSI DAN PENDAPATAN USAHATANI GALUR/VARIETAS PADI DI LAHAN KERING DATARAN RENDAH DI KABUPATEN MERAUKE - Frans Palobo; Batseba Tiro; Siska Tirajoh (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
Income has a close relationship with the level of production achieved, if production increases, income also tends to increase. In addition, the amount of farmers' income depends on the prevailing price level. High or low income is influenced by production and price levels. The aim is to analyze the production and income of rice farming lines/varieties in lowland land agroecosystems. The activity was carried out on the dry land of the IP2TP experimental garden in Merauke Regency. The demonstration plot starts from January to April 2020. The design of the activities used is farming analysis on the four (4) lines and three (3) rice varieties, namely the four new high-yielding lines (1) BP15886M-12D-SKI-5-2_1. (2) BP5478-1F-KN-19-1-2-KLT-2*-SKL-1*8. (3) CRS1291. (4) CRS850, the comparators were Inpago 11, Inpago 12 and Inpara 8. The R/C value for each treatment of the BP15886M-12D-SKI-5-2_1 line had an R/C value of 1.47 TIH 3.58. Line BP5478-1F-KN-19-1-2-KLT-2*-SKL-1*8 R/C value 1.40 TIH 3.75. CRS1291 line R/C value 1.37 TIH 3.84. CRS850 line R/C 1.43 TIH 3.67, Inpago 11 variety R/C 1.83 TIH 2.87, Inpago 12 variety R/C 2.07 TIH 2.54 and Inpara 8 variety R/C 1.70 TIH 3.09.